Relationship between depression, work, and grade of impairment in leprosy - Corrêa, Bruna Janerini; Marciano, Lúcia Helena Soares Camargo; Nardi, Susilene Tonelli; Marques, Tatiani; Assis, Thássia Ferraz de; Prado, Renata Bilion Ruiz (Acta Fisiátrica, 2014)
Depression is the most common psychiatric disorder in leprosy and with high depressive symptoms. Objective: The aim of this study was to determine the prevalence and frequency of depressive symptoms and their relationship to WHO impairment grading (IG), and sociodemographic variables. Method: We applied a survey containing sociodemographic, clinical aspects and IG. The original scale of the BDI was applied to identify the frequency of depressive symptoms (21 items), as well as the cognitive subscale BDI-Short Form-BDI-SF (items 1-13), recommended to assess depressive symptoms in individuals with defined pathologies. Descriptive statistical analysis was used, with the frequency distribution to characterize the sample, and to the intersection of the variables, the Chi-square Test-corrected (Yates) was applied, considering significant results p - value < 0.05. Results: 130 patients who have or have had leprosy were evaluated. The mean age of patients was 49.64 (SD = 14.04). There was a predominance of males (64.6%), those living with family (87.7%), with incomplete primary education (66.2%), stable civil union (61.6%), which did not work (75.4%) and receive retirement or health aid (63.9%). Regarding clinical aspects, 94.5% were multibacillary, 74.6% had multidrug therapy and most have loss of protective sensation and/or deformities (31.5% IG1; 37 % IG2). Among the cases evaluated, 43.1% had depressive symptoms of moderate to severe intensity. There was no significant correlation between BDI-SF and IG (p - value = 0.950). However, the individuals without an occupation or job (“which did not work”) were associated with depressive symptoms (BDI-FS; p- value < 0.05). Somatic apprehension was the most frequent symptom (80.7%), followed by difficulty with work (78.5%), irritability (68.5%), fatigue (67.7%), self-blame (62.3%) and tearfulness (60%). Conclusion: It is concluded that moderate and severe depressive symptoms assaulted 43.1% of the cases evaluated, regardless of whether or not physical disabilities (IG1 and 2). Individuals who did not work were the most affected by depressive symptoms compared to those who had some sort of occupation.